ChemInform Abstract: NH4I‐Mediated Three‐Component Coupling Reaction: Metal‐Free Synthesis of β‐Alkoxy Methyl Sulfides from DMSO, Alcohols, and Styrenes. Issue 28 (July 2015) - Gao, Xiaofang; Pan, Xiaojun; Gao, Jian; Jiang, Huanfeng; Yuan, Gaoqing; Li, Yingwei
Abstract A novel method to synthesize β‐alkoxy methyl sulfides is developed via NH4I‐mediated three‐component oxysulfenylation reaction of styrenes with DMSO and alcohols.